Charge Sharing Suppression in Single Photon Processing Pixel Array - Suliman Abdel Rahman Abdalla (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2017)
This paper proposes a mechanism for suppression of charge sharing in single photon processing pixel array by introducing additional circuit. The idea of the proposed mechanism is that in each pixel only analog part will introduced, the digital part is shared between each four pixels, this leads to reduce the number of transistors (area). By having communication pixels, a decision that which one of the neighboring pixels shall collect the distributed charges is taken. The functionality, which involves analog and digital behaviors, is modeled in VHDL.